Analisis Finansial Usaha Lebah Madu (Studi Kasus di Pusat Perlebahan Halmahera, Desa Linaino, Provinsi Maluku Utara) - Jan E. Papilaya; Grace A.J. Rumagit; Lyndon R.J. Pangemanan; Martha Sendow (COCOS, 2015)
ABSTRACTJan Edmond Papilaya. Financial Analysis of Honeybee Business (Case Study at Halmahera Honeybee Center, Linaino Village, North Molluccas Province) under the guidance of Grace A.J. Rumagit as a Chairman, Lyndon R.J. Pangemanan and Martha M. Sendow as Members)The objective of this research is to know the financial feasibility of Halmahera Honeybee Center, in Linaino Village, North Mollucas Province.The data collection has been started since August 2014, for 3 months. The obtained data were primary and secondary data, primary data was obtained by interviewing the owner of Halmahera Honeybee Center, and secondary data was obtained from the literature that related with honeybee business. The methods that are used to analyze are feasibility analysis to analyze Net Present Value, Internal Rate of Return, Net Benefit/Cost, and Break Event Point.The research showed that the honeybee business in Halmahera Honeybee Center was feasible financially. It could be seen from Net Present Value that was positive (57.659.816,77), Internal Rate of Return was 50.5%, Net Benefit/Cost was 2.34, and Break Event Point was 2 years 1 months 28 days